1999
DOI: 10.1103/physrevlett.82.2693
|View full text |Cite
|
Sign up to set email alerts
|

Thin Nematic Films: Metastability And Spinodal Dewetting

Abstract: We present new results about the stability of 5CB nematic films spun cast onto silicon wafers. We observe experimentally the dewetting of thin films while thick ones remain stable. We interpret this behavior as a competition between elasticity and van der Waals forces. At later stages, the experimentally observed dewetting instability leads to the formation of structures (islands) which grow and finally merge to form a film of uniform thickness. We show that the islands' characteristic size L͑t͒ scales as t 1͞… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
118
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(131 citation statements)
references
References 22 publications
(24 reference statements)
12
118
0
1
Order By: Relevance
“…The experimental scaling exponent, 0.63 Ϯ 0.01, is similar to that predicted for the characteristic size of growing holes in 2D (24,25), where the limiting case of 2͞3 corresponds to a regime of strong slippage, implying that the extra surface energy is dissipated completely within intermolecular interactions.…”
Section: D Structuressupporting
confidence: 57%
“…The experimental scaling exponent, 0.63 Ϯ 0.01, is similar to that predicted for the characteristic size of growing holes in 2D (24,25), where the limiting case of 2͞3 corresponds to a regime of strong slippage, implying that the extra surface energy is dissipated completely within intermolecular interactions.…”
Section: D Structuressupporting
confidence: 57%
“…The forces are long-ranged in systems with soft modes, such as critical simple fluids [2,3] and liquid crystals [4,5], with the decay law and amplitude modulated by various surface effects [3,6,7]. Recent evidence [8,9,10] supports the view that the interaction is ubiquitous in correlated fluids [11].In this Letter, we address the effect in structured fluids above the isotropic-lamellar (I-L) transition. The model system we consider has two characteristic lengths, which describe decay and oscillation of the correlation function.…”
mentioning
confidence: 76%
“…The competition of attractive van der Waals forces and short range repulsive forces, like Born repulsion, can produce complex instabilities in layers of thin liquid films on solid substrates. Experimental studies have shown this behavior for polymer films [66,81,87,88,101], liquid crystal films [58,93,94], liquid metals [29,58] and evaporating films [41,76]. During these dewetting processes, large droplets are formed which are connected by ultra-thin films.…”
Section: Dewetting Filmsmentioning
confidence: 99%